Biological and molecular variation amongst Australian Turnip mosaic virus isolates. (30th January 2015) - Nyalugwe, E. P.; Jones, R. A. C.; Barbetti, M. J.; Kehoe, M. A.
Abstract : Turnip mosaic virus (TuMV) causes crop losses worldwide. Eight Australian TuMV isolates originally obtained from five different species in two plant families were inoculated to 14 plant species belonging to four families to compare their host reactions. They differed considerably in virulence in Brassicaceae crop species and virus indicator hosts belonging to three other families. The isolates infected most Brassica species inoculated, but not Raphanus sativus, usually causing systemic mosaic symptoms, so they resembled TuMV biological host type [B]. Whole genome sequences of seven of the Australian isolates were obtained and had lengths of 9834 nucleotides (nt). When they were compared with 37 non‐recombinant TuMV genomes from other continents and another whole genome from Australia, six of them formed an Australian group within the overall world‐B phylogenetic grouping, while the remaining new genome sequence and the additional whole genome from Australia were part of the basal‐B grouping. When the seven new Australian genomes and the additional whole genome from Australia were subjected to recombination analysis, six different recombination events were found. Six genomes contained one or two recombination events each, but one was non‐recombinant. The non‐recombinant isolate was in the Australian grouping within the overall world‐B group while the remaining recombinant isolates were in the basal‐B and world‐B phylogenetic groups.